Management of Myocardial Revascularization in Patients With Stable Coronary Artery Disease Undergoing Transcatheter Aortic Valve Implantation. (20th December 2022) - Costa, Giuliano; Pilgrim, Thomas; Amat Santos, Ignacio J.; De Backer, Ole; Kim, Won-Keun; Barbosa Ribeiro, Henrique; Saia, Francesco; Bunc, Matjaz; Tchetche, Didier; Garot, Philippe; Ribichini, Flavio Luciano; Mylotte, Dzxcfewarren; et al.
Abstract : Background: The best management of stable coronary artery disease (CAD) in patients undergoing transcatheter aortic valve implantation (TAVI) is still unclear due to the marked inconsistency of the available evidence. Methods: The REVASC-TAVI registry (Management of Myocardial Revascularization in Patients Undergoing Transcatheter Aortic Valve Implantation With Coronary Artery Disease) collected data from 30 centers worldwide on patients undergoing TAVI who had significant, stable CAD at preprocedural work-up. For the purposes of this analysis, patients with either complete or incomplete myocardial revascularization were compared in a propensity score matched analysis, to take into account of baseline confounders. The primary and co-primary outcomes were all-cause death and the composite of all-cause death, stroke, myocardial infarction, and rehospitalization for heart failure, respectively, at 2 years. Results: Among 2407 patients enrolled, 675 pairs of patients achieving complete or incomplete myocardial revascularization were matched. The primary (21.6% versus 18.2%, hazard ratio‚ 0.88 [95% CI, 0.66–1.18]; P =0.38) and co-primary composite (29.0% versus 27.1%, hazard ratio‚ 0.97 [95% CI, 0.76–1.24]; P =0.83) outcome did not differ between patients achieving complete or incomplete myocardial revascularization, respectively. These results were consistent across different prespecified subgroups of patients (< or >75 years of age, Society of Thoracic Surgeons score > or <4%, angina at baseline, diabetes, left ventricular ejection fraction > or <40%, New York Heart Association class I/II or III/IV, renal failure, proximal CAD, multivessel CAD, and left main/proximal anterior descending artery CAD; all P values for interaction >0.10). Conclusions: The present analysis of the REVASC-TAVI registry showed that, among TAVI patients with significant stable CAD found during the TAVI work-up, completeness of myocardial revascularization achieved either staged or concomitantly with TAVI was similar to a strategy of incomplete revascularization in reducing the risk of all cause death, as well as the risk of death, stroke, myocardial infarction, and rehospitalization for heart failure at 2 years, regardless of the clinical and anatomical situations.